2017
DOI: 10.1212/wnl.0000000000003957
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and outcome after revascularization for symptomatic carotid artery stenosis

Abstract: BMI is not associated with periprocedural risk of stroke or death; however, BMI 25-<30 is associated with lower postprocedural risk than BMI 20-<25. These observations were similar for CAS and CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Thirty day death/stroke remained significantly higher when CAS was performed 8e14 days after symptom onset (8.1%) vs. 3.4% after CEA (OR 2.42, 95% CI 1.0e5.7; p ¼ .04) 114. A second meta-analysis (n ¼ 138) included symptomatic CREST patients 119. Thirty day death/stroke after CAS less than seven days after symptom onset was 8.4% vs. 1.3% after CEA (OR 6.51, 95% CI 2.0e21.21; p ¼ .002).…”
mentioning
confidence: 99%
“…Thirty day death/stroke remained significantly higher when CAS was performed 8e14 days after symptom onset (8.1%) vs. 3.4% after CEA (OR 2.42, 95% CI 1.0e5.7; p ¼ .04) 114. A second meta-analysis (n ¼ 138) included symptomatic CREST patients 119. Thirty day death/stroke after CAS less than seven days after symptom onset was 8.4% vs. 1.3% after CEA (OR 6.51, 95% CI 2.0e21.21; p ¼ .002).…”
mentioning
confidence: 99%
“…Fourth, the assessment of the relationship between volume and outcome is hampered since not all studies adjusted for characteristics that are known to influence outcome following carotid revascularization (Appendix Tables 5-6). 6,6365…”
Section: Discussionmentioning
confidence: 99%
“…18 In the patients accepting carotid artery stenting or carotid endarterectomy for symptomatic carotid artery stenosis, BMI is not a periprocedural risk of stroke or death; however, overweight patients were associated with lower post procedural risk than that in normal weight group. 19 Obesity was associated with lower risks in cardiac surgery, as showing a "U-shape" association between mortality and BMI classes which was observed in the cohort study including 557,720 patients. 20 Study showed that BMI ≥40.0 was an independent risk factor for longer length of stay.…”
Section: Obesity and T2dmentioning
confidence: 70%